2018
DOI: 10.24198/sosiohumaniora.v20i1.16141
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Usaha Pembiakan Sapi Potong Pada Pola Kemitraan Antara Korporasi Dengan Peternak Rakyat

Abstract: Kebijakan Permentan nomor 2/2017 tentang rasio importasi sapi bakalan dan indukan, mengharuskan perusahaan penggemukan melakukan usaha pembiakan serta bermitra dengan peternakan rakyat. Sejauhmana kebijakan ini dapat direalisasikan perlu kajian usaha pembiakan dan penggemukan merupakan dua usaha yang sangat berbeda. Tujuan Penelitian ini adalah untuk mengetahui apakah usaha pembiakan sapi potong dengan pola kemitraan antara korporasi dengan peternakn rakyat dapat dilaksanakan sesuai dengan kebijakan pemerintah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…In addition, the bank is also less interested in the breeding partnership pattern because a long time will lead to a significant risk of failure. So from the three partnership patterns, the breeding is a pattern that cannot do intensively; the profit level is negative [7] so that it is less or even not attractive to farmers or banks. At the same time, the beef cattle breeding business, which is expected to produce superior breeds, is one strategy that can reduce and even remove dependence on imports of beef and feeder cattle.…”
Section: Community Beef Cattle Breeder Partnership Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the bank is also less interested in the breeding partnership pattern because a long time will lead to a significant risk of failure. So from the three partnership patterns, the breeding is a pattern that cannot do intensively; the profit level is negative [7] so that it is less or even not attractive to farmers or banks. At the same time, the beef cattle breeding business, which is expected to produce superior breeds, is one strategy that can reduce and even remove dependence on imports of beef and feeder cattle.…”
Section: Community Beef Cattle Breeder Partnership Patternmentioning
confidence: 99%
“…The obstacles faced by people's farmer beef cattle in partnering and operating can be minimized through partnerships with feedlot companies. So that the good advantages of the CSV partnership concept can be elaborated when compared to ordinary partnerships, as shown in * Elaboration from : [23], [13], [10], [11], [15], [16], [17], [18], [19], [20], [21], [7], [24], [25], [26], [27], [28] In creating shared value in CSV, companies can carry out activities such as social business. With the development of the CSV concept, social challenges are at the heart of business strategies and opportunities in creating value for society.…”
Section: Breeding Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obstacles to this feedlot with the fattening business are limiting cages and places for rearing and fattening. Tawaf (2018) showed that limiting cages dan land for fattening is a big problem. Feedlot companies must provide new land or place for imported heifers but require high operational costs, especially in the large quantities of imports.…”
Section: Introductionmentioning
confidence: 99%
“…In Madura, the practice of beef cattle sharing is a form of philanthropy in the economic field. The practice of partnership patterns in cattle in Indonesia includes partnerships that produce calves, feeder cattle and ready-to-be beef cattle (Tawaf, 2018). The cattle sharing system in Madura has its uniqueness compared to other areas in Indonesia (Djaelani et al, 2009); Ibrahim et al, 2013;Novra, 2015).…”
Section: Introductionmentioning
confidence: 99%